Entre mar e terra: um estudo sobre a Festa de São Padro em Tambaú - Andrade, Cleomar Felipe Cabral Job de (2011)
Tambaú area today highly valued the coast of João Pessoa - PB, until the early 1960s, was a residential area, inhabited by fishing communities and livestock breeding. In recent decades, Tambaú has undergone many changes, assuming an important commercial nature. This region has a very rich history in relation to popular culture, may also noted the realization of one of major festivities in the life of the ancient inhabitants of the region: the Festival of St. Peter (Festa de São Pedro), or, as is also called the Procession of St. Peter (Procissão de São Pedro), this work seeks to understand the process of organizing, conducting and processing of the Festival of St. Peter, focusing on the interaction of the various groups involved and, more specifically, watching how the relationships of class, status and prestige interfere with the organization and implementation of the festival. We used the method of participatory research, with records in the usual cultural contexts through handwritten notes, audio recorder and photos. Were also used informal conversations and interviews supported in theme routes. It was observed that the festival are configured in deep socio-cultural codes in geographic areas, comprised of the particularities of each social context, and they enable and consist of celebrations, but also by power relationships, including processes of approximation and detachment, inclusion and exclusion of individuals or social groups. In Tambaú, the festival organized by fishermen devotional also strengthens, rebuilds and takes collective biographical objects and places, beyond the bonds of family, friendship and knowledge re-constituted in spaces of work and celebration, at sea and on land.